Unpacking the politics of natural capital and economic metaphors in environmental policy discourse. Issue 2 (3rd March 2016) - Coffey, Brian
ABSTRACT: Economic metaphors – including natural capital, natural assets, ecosystem services, and ecological debt – are becoming commonplace in environmental policy discourse. Proponents consider such terms provide a clearer idea of the 'value' of nature, and are useful for ensuring the environment is given due attention in decision making. Critical discourse analysis highlights the ideological work language does; the way in which we think, write, and talk about the environment has important implications for how it is governed. Consequently, the widespread use of economic metaphors is politically significant. This article discusses how metaphors have been analysed in environmental policy research, surveys the use of prominent economic metaphors in environmental policy, and considers the politics associated with such terms. The uptake of various economic metaphors represents a form of reverse discourse, varies in politically significant ways, and narrows the terms of environmental debate.